1986
DOI: 10.1002/j.1460-2075.1986.tb04209.x
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's paired helical filaments share epitopes with neurofilament side arms.

Abstract: A panel of monoclonal antibodies to neurofilaments have been investigated with regard to the location of their respective epitopes on neurofilament polypeptides and their ability to label the neurofibrillary tangles and paired helical filaments (PHF) which are characteristic of Alzheimer's disease. All of the neurofilament monoclonal antibodies that label tangles and PHF are directed against epitopes in the side arm domains of the two larger neurofilament polypeptides, NF‐H and NF‐M, and do not recognise the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…Many previous studies have suggested that various intermediate filament proteins may be constituents of NFT (3)(4)(5). Our immunological evidence shows that no antibody directed solely against any neuronal or glial intermediate filament protein showed any staining for the ubiquitin-or tau-positive material.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have suggested that various intermediate filament proteins may be constituents of NFT (3)(4)(5). Our immunological evidence shows that no antibody directed solely against any neuronal or glial intermediate filament protein showed any staining for the ubiquitin-or tau-positive material.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies RT97, BF10, 8D8, and 1215 were produced and kindly provided (as ascites fluids) by B. Anderton and colleagues, who showed that they stain the Mr 200,000 and Mr 160,000 neurofilament proteins as well as neurofibrillary tangles (7,9). Monoclonal antibodies 147 and RS18, also provided as ascites fluids by Anderton and colleagues, stain neurofilaments but not tangles (9). Two monoclonal antibodies to the neurofilament Mr 200,000 and Mr 160,000 polypeptides (here designated BM200 and BM160, respectively) were obtained as purified IgG (20 ,g/ml) from Boehringer Mannheim.…”
Section: Methodsmentioning
confidence: 99%
“…(i) Tangles are stained by polyclonal antibodies to microtubule fractions (2, 3) and by polyclonal and monoclonal antibodies to microtubule-associated protein 2 (MAP2) (4,5). (ii) Antibodies to neurofilament proteins, particularly the Mr 200,000 and Mr 160,000 components, stain tangles (6)(7)(8)(9). (iii) Antibodies to partially purified PHF fractions extracted in NaDodSO4 react with no specific proteins in human brain homogenates, including neurofilament proteins, and produce a peculiar smear of immunoreactivity on electrophoretic transfer blots of Alzheimer disease brain homogenates (10).…”
mentioning
confidence: 99%
“…Epitopes in neurofilament (NF) proteins and two microtubule-associated proteins (MAPs), r protein and MAP2, have been detected with monoclonal antibodies (mAbs) in Alzheimer disease (AD) neurofibrillary tangles (NFTs) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Aberrant phosphorylation (3,9), transport (12), proteolysis (13,14), or crosslinking (15) may account for the incorporation of normal proteins or fragments thereof into NFTs.…”
mentioning
confidence: 99%